PARTICULARS OF PURCHASING MEMORIES CULTURAL HERITAGE - Olena Ustymenko (Вісник Харківського національного університету імені В. Н. Каразіна Серія: «Право»)
Introduction. An extremely important role in the formation of Ukraine as an independent European state is played by raising the level of cultural self-awareness of its citizens, and a separate link in this process is occupied by the proper legislative regulation of the exercise of ownership of cultural heritage sites. The analysis of legal acts regulating the legal status and circulation of monuments of cultural heritage shows a certain fragmentation, inconsistency and the presence of conflicts. To date, the problem of legal regulation of certain aspects of the termination of the right to ownership of cultural heritage sites is quite relevant also in the doctrinal aspect. The insufficient number of individual special studies of cultural heritage monuments as objects of property rights in civil science indicates a correlative relationship with the corresponding legislative uncertainty and at the same time emphasizes the urgent practical significance of such theoretical studies. The purpose of the research is to find out the peculiarities of the purchase of monuments of cultural heritage.